Law Enforcement Of Narcotics Laws - Asep Iswahyudi Rachman; Sri Kusriyah (Universitas Islam Sultan Agung, 2020)
This study aims to explore the law enforcement of the Republic of Indonesia Act No. 35 of 2009 on Narcotics by the Directorate of Drug Research at the Central Java Regional Police. An empirical juridical approach is used to study the phenomena that are the focus of research. Data collection techniques using data reduction, data presentation, triangulation and drawing conclusions. The results showed that the narcotics crime in the jurisdiction of the Central Java Regional Police was already at an unsettling stage and not only involved the adult group, but also touched teenagers and children. Law enforcement of Act No. 35 of 2009 concerning Narcotics